1983
DOI: 10.3382/ps.0620397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Canola Meal on the Sensory Quality of Turkey Meat

Abstract: The sensory quality of 4 male and 4 female carcasses of 14-week-old broiler turkeys fed each level of 0, 73, 144, and 211 g Candle canola (low erucic acid, low glucosinolate rapeseed) meal (CM) per kilogram was evaluated by an experienced taste panel. Except for a slightly increased frequency of off-flavors at 73 g/kg diet, no differences in flavor or off-flavors were associated with level of CM in diet. (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Comparison of the Larmond et al (1983) and Salmon et al (1988) studies was possible because they had common methodologies. The approach consisted of oven roasting at 162 to 163'C until an internal breast temperature of 85'C was attained The ballot sheet for both studies was composed of 15-cm unstructured h e scales (Larmond, 1977) including the attributes of flavor and off-flavor.…”
Section: Literature In Briefmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of the Larmond et al (1983) and Salmon et al (1988) studies was possible because they had common methodologies. The approach consisted of oven roasting at 162 to 163'C until an internal breast temperature of 85'C was attained The ballot sheet for both studies was composed of 15-cm unstructured h e scales (Larmond, 1977) including the attributes of flavor and off-flavor.…”
Section: Literature In Briefmentioning
confidence: 99%
“…Testing for both studies was done at the Food Research Centre, Ottawa. Results of Larmond et al (1983) Salmon et al (1988) could be due to the use of more experienced panelists.…”
Section: Literature In Briefmentioning
confidence: 99%
See 1 more Smart Citation
“…Triticale varieties have successfully been fed to market turkeys and adult breeder turkey toms (Nakaue et al, 1981;Savage et al, 1984;McGinnis et al, 1985). Larmond et al (1983) and Moran et al (1984) reported that characteristics of cooked meat in market age turkeys are influenced by dietary factors; however, there are no such reports in the literature pertaining to aged breeders. The purpose of this research was to determine the physical and sensory quality of cooked meat from aged breeder turkey toms when fed diets containing varying amounts of triticale, variety Flora.…”
Section: Introductionmentioning
confidence: 91%
“…No such effects were observed when the diets contained 21.0% and 9.0% Canola meal, respectively. LARMOND et al [51] observed a slight increase in off-flavours for turkey meat when 7.3% Canola meal was included in the diet. However this may have been a spurious result since the same work quotes higher inclusion levels (14.4 and 21.1%) to have no such effects.…”
Section: Carcassmentioning
confidence: 99%